Implementasi Metode TOPSIS dalam Sistem Pendukung Keputusan Pemilihan Laptop berdasarkan Spesifikasi - Dian Noviandri; Muhammad Syahrul Wildan; Rimbun Bonatio Cristoper Sagala; Zulya Novriani Karnaen; Syahrul Riza (LKP KARYA PRIMA KURSUS, 2026)
Selecting a laptop that meets user needs is often a challenging problem due to the large number of available alternatives and the variety of criteria that must be considered, such as price, RAM, processor, and storage capacity. The main problem addressed in this study is how to determine the best laptop recommendation objectively and systematically based on these criteria. This study aims to develop a decision support system for laptop selection using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The TOPSIS method is applied because it can identify the best alternative based on its closeness to the positive ideal solution and its distance from the negative ideal solution. The research stages include collecting laptop specification data, determining criteria weights, normalizing the decision matrix, calculating the distance to ideal solutions, and determining preference values and alternative rankings. The results show that the developed system is able to provide accurate and consistent laptop recommendations and is in accordance with the manual calculation of the TOPSIS method. Therefore, this system can assist users in making more effective, efficient, and objective decisions when selecting laptops.